1985
DOI: 10.1152/ajprenal.1985.249.4.f490
|View full text |Cite
|
Sign up to set email alerts
|

Reduced renal blood flow in early cisplatin-induced acute renal failure in the rat

Abstract: Studies were designed to determine the cause of the reduced glomerular filtration rate (GFR) in early cisplatin-induced acute renal failure. Rats were studied 72 h following a single intraperitoneal injection of cisplatin (5 mg/kg) or vehicle (0.9% NaCl). Whole kidney GFR and blood flow were lower in cisplatin-treated animals than in controls (0.30 +/- 0.06 vs. 1.17 +/- 0.06 ml X min-1 X g kidney wt-1 and 5.30 +/- 0.62 vs. 8.25 +/- 0.43 ml X min-1 X g kidney wt-1, respectively; P less than 0.001), as were supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
112
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(117 citation statements)
references
References 0 publications
4
112
1
Order By: Relevance
“…A common adverse side effect of cisplatin treatment is nephrotoxicity. For example, a single intraperitoneal injection of cisplatin (5 mg/kg) induces acute renal failure in a rat model (Winston and Safirstein, 1985). The nephrotoxic effect of cisplatin on the kidney is thought to be mediated in part through the thromboxane A 2 pathway (Jariyawat et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…A common adverse side effect of cisplatin treatment is nephrotoxicity. For example, a single intraperitoneal injection of cisplatin (5 mg/kg) induces acute renal failure in a rat model (Winston and Safirstein, 1985). The nephrotoxic effect of cisplatin on the kidney is thought to be mediated in part through the thromboxane A 2 pathway (Jariyawat et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Although cell death in renal tubules is widely recognized, cisplatin also is expected to disrupt vasculature in the kidneys, leading to hypoperfusion or hypoxia (16). This view is supported by direct evidence from recent studies that detected the staining of outer renal medulla and cortex of cisplatin-treated animals by pimonidazole, a hypoxia-specific dye (6).…”
mentioning
confidence: 92%
“…CP is the inhibitor of desoxyribonucleic acid synthesis (4) and nephrotoxicity of CP seems to be related to reactive oxygen species. Reactive oxygen species, especially the hydroxyl radical, induce lipid peroxidation and cell membrane damage and reduce glomerular filtration rate (GFR) (7)(8)(9). It is reported that CP-induced nephrotoxicity may be ameliorated by scavenging agents such as vitamins E and C, losartan, melatonin, selenium, superoxide dismutase, and erythropoietin (10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%